Effect of Tobacco Stalk Additive Particle Size on the Bond Strength and Formaldehyde Emission of Urea Formaldehyde Bonded Plywood. - Jimenez, Juanito P.
The study investigated the use of native type (Batek) tobacco (Nicotiana tabacum L.) stalk particles from two different mesh sizes ? passing 100 mesh but retained at 200 mesh coded as N-100m (74?149 µm) and passing 200 mesh coded as N-200m (< 74 µm) ? as additive with both extender and filler property, as well as formaldehyde scavenging property in urea-formaldehyde (UF) resins adhesive formulation used to bond veneers [Falcataria moluccana (Miq.) Barneby & J.W. Grimes] into plywood. The effect of tobacco stalk particle (TSP) size on adhesion performance, tensile shear strength (TSS), and wood failure (wF), as well as formaldehyde emission (FE) of three-ply plywood, was investigated and compared with traditional additives such as wheat flour (WF), coconut shell flour (CS), and rice hull flour (RH). The glue-mix containing UF resins with TSP at 8% by mass was blended very well. There is no difference in the TSS and wF of plywood bonded with N-200m TSP as additive compared to commercial UF formulations; however, a significant decrease of TSS and wF was observed with N-100m. The addition of N-200m significantly reduced FE by 23%, 33%, and 44% compared to those of WF-CS, WF-RH, and N-100m, respectively.